Representação do corpo do homem negro na dança: visibilidade e racialização acerca do Grupo de Dança Contemporânea "Filhos de Afrodite" Unemat/Cáceres - MT - Baccin, Adriana Nolibos (2020)
The key point of this research was to identify and analyze the possible conflicts that emerge from the representations of men's bodies in dance, concerning to the differences of gender, race and sexuality. The men who participated in this thesis are part of the contemporary dance group entitled “Filhos de Afrodite” (Sons of Aphrodite) and are/were all academics of the Degree Course in Physical Education at the State University of Mato Grosso (Unemat), University Campus “Jane Vanini” in Cáceres-MT. We have as contribution, to the discussion, the (dis)constructions of masculinity(ies) and femininity(ies), to which the body is genderized and genderizer; the racialization and its imbrications with the sexuality; and, the dance, as a corporeal-social practice historical and culturally systematized. In addition, we intend to think in relation to the constructions of subjectivities, constituents of and about the body of these men. The research is based on constant dialogue with Michel Foucault (2006; 2005; 2004; 1996; 1994; 1987; 1985; 1984) , Judith Lynne Hanna (1999), Raewin Connell (1995a; 1995b; 1993; 1987) Connell and Messerschmidt (2013a), Connell, Hamlin and Vanderberghe (2013b), Connell and Hamlin (2000), Connell and Dowsett (1992), Frantz Fanon (2008); 1980; 1979), Stuart Hall (2005; 2003; 2000; 1997a, 1997b; 1996), among others, which work with dance and the differences marked by racialization, sexuality and the generification of bodies and power relations. As methodological choices, in addition to the updated reference on the themes, strategies were used such as participant observation, questionnaires, conversation circles, and, mainly, field diaries, as well as records of the presentations of the group under study. Race and sexuality, intertwined, led to stigmatization in relation to the body of these men, marking not only the black men of the group as the most sensual and beautiful, reaffirming questions of structural prejudices in relation to the sexualization of the race, but also, the a discussion about the body of these men and the body of the white woman who runs them. Another fundamental issue, which was initially raised, was the affirmation of naturalized gender violence through sexualization with / among the dance group participants, in the Physical Education course at Unemat and in the “evaluations” made by the audience that attended them.